Hysteroscopic sutureless fixation of the levonorgestrel-releasing intrauterine system in the treatment of heavy menstrual bleeding - Shen, Linjiang; Zhang, Juan; Wu, Junjiang; Ye, Mingming; Shao, Hui; Zhang, Feng (Frontiers in Medicine, 2025)
BackgroundThis study investigated the safety and efficacy of hysteroscopic sutureless fixation of the levonorgestrel-releasing intrauterine system (LNG-IUS) for treating heavy menstrual bleeding (HMB), providing a viable therapeutic option for patients at high risk of LNG-IUS expulsion.MethodsNinety patients were enrolled and equally divided into three groups: conventional implantation of LNG-IUS group (control group), hysteroscopic suture fixation of LNG-IUS group (suture fixation group) and hysteroscopic sutureless fixation of LNG-IUS group (sutureless fixation group). The rates of LNG-IUS expulsion and displacement, complication rates, pre- and postoperative menstrual flow, pain scores, and life satisfaction scores were recorded for each of the three groups.ResultsThe LNG-IUS expulsion rate in the sutureless fixation group was 3.3% and the displacement rate was 10%. There was no significant difference compared to the suture fixation group (3.3% LNG-IUS expulsion rate and 16.7% displacement rate in the suture fixation group, p > 0.05). There was a significant difference compared to the control group (13.3% expulsion rate and 23.3% displacement rate in the control group, p < 0.05). There was no significant difference in the rate of postoperative complications among the three groups (p > 0.05). Postoperative menstrual flow was significantly reduced in all three groups (p < 0.05), pain scores were significantly reduced (p < 0.05), and quality of life scores were significantly improved (p < 0.05).ConclusionOur findings indicate that hysteroscopic sutureless fixation of the LNG-IUS is a safe, effective, and minimally invasive surgical procedure to prevent the LNG-IUS expulsion. This procedure leads to a significant reduction in menstrual flow, relieves the symptoms of dysmenorrhea, and improves patient quality of life.